Pedoman Tata Kelola Teknologi Informasi Menggunakan It Governance Design Frame Work (Cobit) Pada PT. X - Purnawan, I Ketut Adi (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 6, No.3 Desember 2015, 2015)
Implementation of  Information Technology (IT) in an organization require significant costs with high risk  of  failure [ 3 ] . Managing data is  a matter that must be done continuously by the organization and accompanied by monitoring and measurement of achievement that has been done as to meet the aspect of integrity, availabl i l i t y . In this study using COBIT as a frame work in preparing the guidelines for information technology governance at PT.  X  on  DS11,  which  focuses  on  management of  data  about  the  level  of  concern  for management (management awareness) and  maturity level (maturity level).  The study and analysis indicates that the level of concern for management (management awareness) PT. X already on a fairly level and maturity level for the current maturity level (as is) at level 3 (defined process) and to the expected level of maturity located at level 5 (optimized). From the overall study results showed that PT. X has recognized that the data is an important organizational asset.